Evaluation Of Impulsivity Symptoms And Family Functioning In Adolescents Diagnosed With Obsessive Compulsive Disorder And Their Mothers - Gonca Ozyurt (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: In a variety of clinic studies, it has been shown that impulsivity is one of the core symptoms of Obsessive-compulsive disorder (OCD). The aim of the present study is comparing the impulsivity symptoms of adolescents who are diagnosed with OCD and their mothers with controls; family functioning is also evaluated. Method: The study group consisted of 31 cases (11-18 years old) diagnosed with OCD. The control group (n=32) comprised patients of other clinics at hospital and was matched for gender and age to the OCD patients. Barrat Impusivity Scale 11 (BIS-11) was used for evaluaitng impulsivity symptoms in adolescents and their mothers. Family Assesssment Device (FAD) was used to examine family functioning. Results:There was no significant difference between sociodemographic data of two groups. When cases and controls were compared with BIS-11; all subscales scores and total score of BIS-11were statistically significant higher in OCD group and also mothers of OCD group had statistically significant higher scores in total score of BIS-11 and subscales except motor impulsivity. Also in comparing the grups with FAD; OCD group had statistically significant higher scores in all subscales except affective responsiveness. Conclusion: OCD is an important chronic psychiatric disorder which affects functionality seriously. Cases diagnosed with OCD and their mothers have more impulsivity symptoms and these symptoms affects family functioning. Further studies are needed to examine genetic and enviromental common risk factors between OCD and impulsivity [JCBPR 2016; 5(2.000): 57-64]